University Teachers' Teaching Style and Their Students' Agentic Engagement in EFL Learning in China: A Self-Determination Theory and Achievement Goal Theory Integrated Perspective - Jiang, Anne Li; Zhang, Lawrence Jun (Frontiers in Psychology, 2021)
As a relatively new dimension of student engagement, agentic engagement has received growing research interest in recent years, as it not only predicts academic achievement and other positive outcomes, but also benefits reciprocal teacher-student relations. In the educational context, teachers’ teaching style exerts a crucial impact on students’ engagement. However, research on how perceived teachers’ teaching style influences students’ agentic engagement is inconclusive. To address this lacuna, this study, taking an integrated perspective that draws on Self-determination Theory and Achievement Goal Theory, investigated the relationship of three types of teaching style (i.e., perceived autonomy support, social relatedness, and controlling) to university students’ agentic engagement in EFL learning in China, especially through the mediation of mastery-approach goals and performance approach goals. Structural equation modeling showed that perceived autonomy support positively predicted agentic engagement through the mediation of mastery-approach goals, whereas perceived controlling negatively predicted agentic engagement through the mediation of performance-approach goals. Comparatively, the relationship of perceived social relatedness to agentic engagement was fully mediated by both mastery-approach and performance-approach goals. After discussing these results, practical implications as well as suggestions for future studies were given.